C terminus of Nce102 determines the structure and function of microdomains in the Saccharomyces cerevisiae plasma membrane - Loibl, Martin; Großmann, Guido (Eukaryotic cell, 2010)
The plasma membrane of the yeast Saccharomyces cerevisiae contains stably distributed lateral domains of specific composition and structure, termed MCC (membrane compartment of arginine permease Can1). Accumulation of Can1 and other specific proton symporters within MCC is known to regulate the turnover of these transporters and is controlled by the presence of another MCC protein, Nce102. We show that in an NCE102 deletion strain the function of Nce102 in directing the specific permeases into MCC can be complemented by overexpression of the NCE102 close homolog FHN1 (the previously uncharacterized YGR131W) as well as by distant Schizosaccharomyces pombe homolog fhn1 (SPBC1685.13). We conclude that this mechanism of plasma membrane organization is conserved through the phylum Ascomycota. We used a hemagglutinin (HA)/Suc2/His4C reporter to determine the membrane topology of Nce102. In contrast to predictions, its N and C termini are oriented toward the cytosol. Deletion of the C terminus or even of its last 6 amino acids does not disturb protein trafficking, but it seriously affects the formation of MCC. We show that the C-terminal part of the Nce102 protein is necessary for localization of both Nce102 itself and Can1 to MCC and also for the formation of furrow-like membrane invaginations, the characteristic ultrastructural feature of MCC domains.